FDI Determinants in Asia: Financial Inclusion and Macroeconomic Stability—A First-Difference GMM Approach - Hopkins Henry Kawaye; Agustina Puji Rahayu; Firsty Ramadhona Amalia Lubis; Nurul Azizah Az Zakiyyah; Selly Kudrati Ningsih; Happy Febrina Hariyani (JAMPE (Journal of Asset Management and Public Economy), 2026)
This study analyses the influence of financial inclusion and macroeconomic variables on Foreign Direct Investment (FDI) in nine Asian countries with the highest FDI performance during 2011–2023. Using secondary data from the World Bank, this research employs a dynamic panel-data approach with the First-Difference Generalised Method of Moments (FD-GMM) to address potential endogeneity issues. The variables examined include inflation, interest rates, trade openness, bank credit financing, and the number of bank branches as proxies for financial inclusion. The results indicate that all variables have a positive and significant effect on FDI inflows. The main contributions of this study lie in three areas. First, this study integrates financial inclusion indicators—specifically bank credit and branch availability—into the analysis of FDI determinants, an area that remains underexplored compared to traditional macroeconomic factors. Second, this study provides empirical evidence from a focused sample of top-performing Asian economies, offering more targeted regional insights into FDI dynamics. Third, by applying the FD-GMM approach, this study enhances methodological robustness by addressing endogeneity and dynamic relationships, which are often overlooked in conventional panel-data analyses. These findings suggest that strengthening financial inclusion alongside maintaining macroeconomic stability can significantly enhance a country's attractiveness to foreign investors. From a policy perspective, governments should improve access to financial services while maintaining macroeconomic stability to foster a more conducive investment climate. These findings also provide empirical evidence for policymakers in emerging Asian economies seeking to design strategies for attracting sustainable foreign direct investment.